The relationship between creativity and the ability to solve HOTS science problems - Ardilla Dinova; Dea Mustika (Inovasi Kurikulum, 2025)
The ability to solve Higher Order Thinking Skills (HOTS) questions in elementary science remains a challenge, as many students struggle with tasks requiring higher-level reasoning. This issue is critical because mastering HOTS is a key demand of the 21st-century curriculum, which emphasizes analytical, critical, and creative skills as essential competencies. Creativity is assumed to be one of the factors influencing this ability. This study aimed to investigate the relationship between creativity and the ability to solve HOTS science questions among fifth-grade students at SD Negeri 003 Tambusai. A quantitative method with a correlational approach was employed, involving a total sample of 79 students selected through a total sampling method. Data were collected using a creativity questionnaire and a HOTS-based science test. The analysis included normality testing, linearity testing, Pearson correlation, and the coefficient of determination. The findings showed a positive and moderate correlation between creativity and the ability to solve HOTS science questions, which was statistically significant. Although other factors may also affect this ability, creativity was found to make a meaningful contribution. The study concludes that creativity plays a crucial role in enhancing higher-order thinking skills, and it recommends that teachers integrate strategies that foster creativity in science education.   Abstrak Kemampuan penyelesaian soal Higher Order Thinking Skills (HOTS) pada mata pelajaran IPA di sekolah dasar perlu ditingkatkan karena masih banyak murid yang kesulitan mengerjakan soal yang memerlukan penalaran tingkat tinggi. Kondisi ini penting untuk diteliti karena penguasaan HOTS merupakan tuntutan kurikulum abad ke-21 yang menekankan kemampuan analitis, kritis, dan kreatif sebagai bekal menghadapi tantangan global. Kreativitas diduga menjadi salah satu faktor yang memengaruhi kemampuan ini. Penelitian ini bertujuan mengetahui hubungan antara kreativitas dengan kemampuan penyelesaian soal HOTS IPA murid kelas V SD Negeri 003 Tambusai. Penelitian menggunakan metode kuantitatif dengan pendekatan korelasional. Sampel berjumlah 79 murid yang dipilih dengan teknik total sampling. Instrumen yang digunakan berupa lembar kuesioner kreativitas dan lembar tes kemampuan penyelesaian soal HOTS IPA, dengan analisis data meliputi uji normalitas, uji linearitas, korelasi Pearson, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa terdapat hubungan positif dengan kekuatan sedang antara kreativitas dan kemampuan penyelesaian soal HOTS IPA, yang signifikan secara statistik. Kreativitas berkontribusi terhadap kemampuan penyelesaian soal HOTS IPA, meskipun masih ada faktor lain yang memengaruhinya. Disimpulkan bahwa kreativitas berperan penting dalam meningkatkan keterampilan berpikir tingkat tinggi, sehingga guru disarankan mengintegrasikan strategi pembelajaran yang mendorong kreativitas dalam pembelajaran IPA. Kata Kunci: HOTS; kreativitas; penyelesaian-masalah; sains; sekolah dasar